Dressed to drill - Carlisle, Kate, 1951- (Carlisle, Kate, 1951- Fixer-upper mystery., 2023)
When a dead body halts her renovation of an old Victorian church, Shannon Hammer discovers the church is hiding a century of secrets and must figure out which one someone with a screw loose would kill to protect.